2020
DOI: 10.1039/c9sc05060d
|View full text |Cite
|
Sign up to set email alerts
|

Facile in situ reductive synthesis of both nitrogen deficient and protonated g-C3N4 nanosheets for the synergistic enhancement of visible-light H2 evolution

Abstract: Nitrogen deficient and protonated g-C3N4 was fabricated by the conjoint protocol utilizing NH4Cl as gas template and H3PO2 as doping agent, leading to enhanced visible-light harvesting and charge carrier separation to achieve efficient H2 evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 50 publications
(101 reference statements)
4
42
0
Order By: Relevance
“…12 Li et al reported both protonated and nitrogendeficient g-C 3 N 4 and demonstrated that nitrogen vacancies accompanied by additional protons could lead to significant photocatalytic H 2 evolution enhancements. 13 The above works confirm that N-deficient g-C 3 N 4 materials can exhibit excellent photoelectric properties. However, most reported N-deficient g-C 3 N 4 materials did not possess a 2D porous nanosheet structure.…”
Section: ■ Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…12 Li et al reported both protonated and nitrogendeficient g-C 3 N 4 and demonstrated that nitrogen vacancies accompanied by additional protons could lead to significant photocatalytic H 2 evolution enhancements. 13 The above works confirm that N-deficient g-C 3 N 4 materials can exhibit excellent photoelectric properties. However, most reported N-deficient g-C 3 N 4 materials did not possess a 2D porous nanosheet structure.…”
Section: ■ Introductionsupporting
confidence: 62%
“…It is worth noting that the peak of (002) shifted slightly from 27.7 to 27.4°, indicating an increased interlayer distance from 0.322 to 0.325 nm in CNNS. 13,25,26 Remarkably, the peak of (100) is stronger for CNNS, which is attributed to the more ordered arrangement of triazine and the increase of planar size of the layers. 27 In our case, the intercalation of lithium chloride ions endows the synthesized CNNS with a more ordered triazine ring arrangement, a larger in-plane area, and a larger interlayer distance, which is conducive to the formation of the 2D ultrathin g-C 3 N 4 nanosheet.…”
Section: ■ Experimental Sectionmentioning
confidence: 96%
“…9,10 Recently, a combination of inorganic semiconductors and organic components has been proposed as a feasible strategy to improve the photocatalytic efficiency of photocatalysts. [11][12][13] Among them, covalent-organic frameworks (COFs), porous and crystalline organic semiconductors, are attractive building blocks for the construction of photocatalysts, owing to their high visible light absorption capacity and fast charge-carrier mobility. [14][15][16] In particular, their structure, band position and band gap can be precisely designed, which provides an ideal scaffold to accurately integrate photocatalytic units into Zscheme heterojunctions with periodic skeletons and predictable manner.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above-mentioned three strategies, the defect engineering and elemental doping have also been intensively used to increase the photocatalytic activity of g-C 3 N 4 via modulating its bandgap, band positions, and optical absorption, etc. ,, ,, In recent years, various nonmetal and metal elements, such as Fe, K, Na, Pt, B, , Br, C, Cl, F, I, N, O, , P, , and S, , have been used and reported to dope g-C 3 N 4 for photocatalysis. For example, Shen et al simultaneously introduced both B dopants and N defects into g-C 3 N 4 by calcining the mixture of g-C 3 N 4 and NaBH 4 under a N 2 atmosphere. , The UV–visible absorption spectra and VB XPS spectra as well as the DFT calculations confirmed that the B-doped and N-deficient g-C 3 N 4 possessed largely narrowed bandgap and modulated band positions, compared with pristine g-C 3 N 4 .…”
Section: Strategies To Obtain Broadband G-c3n4-based Photocatalysts A...mentioning
confidence: 99%